Lipid Liquid Crystal Nanoparticles: Promising Photosensitizer Carriers for the Treatment of Infected Cutaneous Wounds - Muhammed Awad; Zlatko Kopecki; Timothy J. Barnes; Anthony Wignall; Paul Joyce; Nicky Thomas; Clive A. Prestidge (MDPI AG, 2023)
Cutaneous chronic wounds impose a silent pandemic that affects the lives of millions worldwide. The delayed healing process is usually complicated by opportunistic bacteria that infect wounds. Staphylococcus aureus is one of the most prevalent bacteria in infected cutaneous wounds, with the ability to form antibiotic-resistant biofilms. Recently, we have demonstrated the potential of gallium protoporphyrin lipid liquid crystalline nanoparticles (GaPP-LCNP) as a photosensitizer against S. aureus biofilms in vitro. Herein, we investigate the potential of GaPP-LCNP using a pre-clinical model of infected cutaneous wounds. GaPP-LCNP showed superior antibacterial activity compared to unformulated GaPP, reducing biofilm bacterial viability by 5.5 log10 compared to 2.5 log10 in an ex vivo model, and reducing bacterial viability by 1 log10 in vivo, while unformulated GaPP failed to reduce bacterial burden. Furthermore, GaPP-LCNP significantly promoted wound healing through reduction in the bacterial burden and improved early collagen deposition. These findings pave the way for future pre-clinical investigation and treatment optimizations to translate GaPP-LCNP towards clinical application.